Características estruturais dos serviços de saúde bucal na atenção primária do Brasil - Maria Tereza de Abreu Scalzo (2019)
The National Programme for Improving Access and Quality of Primary Care (PMAQAB in portuguese) seeks to induce the expansion of access and improvement of the quality of basic care, with a guarantee of a quality standard allowing greater transparency and effectiveness of the governmental actions directed to Basic Health Care. The aim of this study was to describe the structure of oral health services in primary health care in Brazil. This cross-sectional study evaluated 16,202 oral health services, adhering to the second cycle of the ‘National Program for Improving Access and Quality of Primary Care’ (PMAQ-AB), regarding 22 pieces of dental equipment and 25 dental supplies. The presence of each piece of equipment/dental supply generated a score for services. The sum of these scores was compared among different regions in Brazil. Quantitative data were described by quartiles and categorical data by frequencies, using the SPSS, version 25. Most evaluated services presented adequate equipment in use conditions and sufficient dental supplies for primary oral health care. Data also showed a lack of some equipment, such as X-rays, bicarbonate jet, and ultrasound devices, while dental supplies lacked amalgam (capsule and manual preparation), anesthesia without vasoconstrictors, and intracanal medication. The services presented a median of 14 pieces of equipment and 22 dental supplies. Of the Brazilian regions, the South presented the largest median, while the North and Northeast regions presented the smallest. The oral health services presented dental offices in good conditions of equipment/dental supply availability to perform clinical activities. However, differences in the structure of services between the Brazilian regions are still observed